Understanding the Early Impacts of the COVID-19 Pandemic on Brain Injury Associations Across Canada: A Qualitative Study - Ana Paula Salazar PhD; Sophie Lecours PhD; Lisa Engel PhD; Monique A. M. Gignac PhD; Shlomit Rotenberg PhD; Sareh Zarshenas PhD; Michelle McDonald BA; Carolina Bottari PhD (SAGE Publishing, 2023)
The COVID-19 pandemic has increased challenges for people living with brain injury and community associations to support this vulnerable population. This study aimed to gain an in-depth understanding of the challenges faced by brain injury survivors during the first year of the pandemic and how community brain injury associations adapted their services to respond to these needs. Findings from seven focus-group with 31 representatives of Canadian brain injury associations revealed 4 main themes: (1) Addressing evolving client needs; (2) Keeping clients safe; (3) Challenges and opportunities navigating the digital world; and (4) Sustaining brain injury associations in the face of uncertainties and disruptions. To comply with public health measures, associations reported pivoting their service delivery online, despite recognizing the difficulties this could create for many brain injury survivors in accessing and using technology. Our findings also highlight concrete directions for not-profit organizations providing instrumental help with activities, acting as a liaison and interpreter of public health guidelines, and in connecting with clients using technology while handling potential cognitive and technological challenges. Addressing these issues has the potential to protect people living with brain injury and community associations from external threats, like pandemics, in the future.